2009
DOI: 10.2903/j.efsa.2009.1017
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite as undesirable substances in animal feed ‐ Scientific Opinion of the Panel on Contaminants in the Food Chain

Abstract: SUMMARYNitrite is formed naturally by the nitrogen cycle during the process of nitrogen fixation and it is subsequently converted to nitrate, a major nutrient assimilated by plants. Two main nitrite salt forms occur, namely sodium and potassium nitrite.In animal tissues, nitrite is naturally present mainly as the result of endogenous nitrate conversion. Animal feed represents a natural source of exogenous nitrite and because of its potential for toxicity at excessive levels of intake, the Directive (EC) No 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…In many bacteria, analogs of glmS have multiple downstream integration-specific sites (Tn7) ( Choi and Kim, 2009 ), which may explain the mobility of this gene. Explaining the mobility of napA is less straightforward, but this gene is known to encode a nitrate reductase in Campylobacter ( Pittman et al, 2007 ) in microaerobic conditions, which may be ecologically significant as the accumulation of nitrate in slurry, straw, and drainage water can be potentially toxic to livestock mammals ( Alexander et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In many bacteria, analogs of glmS have multiple downstream integration-specific sites (Tn7) ( Choi and Kim, 2009 ), which may explain the mobility of this gene. Explaining the mobility of napA is less straightforward, but this gene is known to encode a nitrate reductase in Campylobacter ( Pittman et al, 2007 ) in microaerobic conditions, which may be ecologically significant as the accumulation of nitrate in slurry, straw, and drainage water can be potentially toxic to livestock mammals ( Alexander et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The EFSA Scientific Panel on Contaminants in the Food Chain (CONTAM Panel) has produced three opinions relevant to sodium and potassium nitrites (EFSA CONTAM Panel, 2008, 2009b, 2010b.…”
Section: Information On Existing Authorisations and Evaluationsmentioning
confidence: 99%
“…milk, meat and eggs) is only (2.9%) of the total daily dietary exposure to nitrite. The CONTAM Panel concluded that 'such low nitrite levels in fresh animal products do not raise any concern for human health' (EFSA CONTAM Panel, 2009b).…”
Section: Information On Existing Authorisations and Evaluationsmentioning
confidence: 99%
“…Nitrate poisoning has been recorded in numerous studies (1,2) and it can happen in man and animals (3). Through entero hepatic metabolism of nitrate due to nitrite being an intermediate may cause poisoning of nitrate (4).…”
Section: Introductionmentioning
confidence: 99%
“…The iron atoms in hemoglobin oxidized by nitrites converted from ferrous (Fe +2 ) to ferric iron (Fe +3 ), which leads to its inability to carry oxygen, this mechanism can lead to which is called methemoglobinemia it is a generalized deficiency of oxygen in organ tissue and a serious case, usually nitrite converts to ammonia, but if there is an increase in nitrite than can be converted, slowly the human and animal suffers from a deficiency of oxygen (5,6). In human nitrate is reduced to nitrite before ingestion in saliva and in the gastrointestinal tract (3,7). In ruminants; cattle, sheep, and goat, the conversion of nitrate to nitrite is carried out by rumen bacteria (7,8).…”
Section: Introductionmentioning
confidence: 99%